2010
DOI: 10.1677/joe-09-0275
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining the male germline: regulation of spermatogonial stem cells

Abstract: Spermatogonial stem cells (SSCs) are a self-renewing population of adult stem cells capable of producing progeny cells for sperm production throughout the life of the male. Regulation of the SSC population includes establishment and maintenance of a niche microenvironment in the seminiferous tubules of the testis. Signaling from somatic cells within the niche determines the fate of SSCs by either supporting self-renewal or initiating differentiation leading to meiotic entry and production of spermatozoa. Despi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 95 publications
0
62
0
1
Order By: Relevance
“…In addition, 30-35% of Gdnf global Het mice had renal defects (49,53). In vitro studies since have demonstrated that GDNF regulates expression of genes in SSCs that influence their self-renewal and differentiation (1,3,54). Because GDNF has a critical role in multiple developmental processes in addition to spermatogenesis, it remained uncertain whether the perturbations of SSC development in vivo were due to direct effects on SSCs or indirect effects of total GDNF levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, 30-35% of Gdnf global Het mice had renal defects (49,53). In vitro studies since have demonstrated that GDNF regulates expression of genes in SSCs that influence their self-renewal and differentiation (1,3,54). Because GDNF has a critical role in multiple developmental processes in addition to spermatogenesis, it remained uncertain whether the perturbations of SSC development in vivo were due to direct effects on SSCs or indirect effects of total GDNF levels.…”
Section: Discussionmentioning
confidence: 99%
“…They are a minor fraction of the undifferentiated spermatogonia in the basal compartment. The other undifferentiated spermatogonia (progenitors) give rise to differentiating spermatogonia that proliferate mitotically to progress on a developmental pathway toward becoming spermatocytes (3,4). Our current understanding of the progression of SSCs to differentiating spermatogonia comes mainly from cell kinetic studies, germ cell transplantation assays, and the use of molecular markers that identify different populations of spermatogonia.…”
mentioning
confidence: 99%
“…The numbers of these stem cells in testes is approximately 0.03 % of the total testicular cell population in the adult mouse [28,36]. Additionally, the establishment and maintenance of a niche's microenvironment in the seminiferous tubules of the testis is important to regulate the SSC population and its function [4]. These cells are located close to several supporting somatic cells and the basement membrane or extracellular matrix (ECM) of seminiferous tubules, which may contribute to the formation of the SSC niche.…”
Section: Introductionmentioning
confidence: 99%
“…In both cases, they are not produced in greater differentiation (Type A 1 -A 4 , Intermediated, spermatocytes and spermatids; Caires et al, 2010). A key step in studying the biology of SSCs is to determine their gene expression profile.…”
Section: Characterization Of Spermatogonial Stem Cellsmentioning
confidence: 99%
“…However, a scarce knowledge of molecular markers has been accumulated in recent years (Kokkinaki et al, 2010). Some research groups have demonstrated that glial cell-.derived neurotrophic factor (GDNF) is the most essential factor for SSC self-renewal and in vitro maintenance in rodents (Caires et al, 2010;Ryu et al, 2005;Meng et al, 2000;Kubota et al, 2004a,b;Kanatsu-Shinohara et al, 2005;Kanatsu-Shinohara et al, 2008;and Braydish-Stalle et al, 2005) and that GDNF receptor (GFRA1) is expressed by SSC/progenitor cells (Naughton et al, 2006;Hofmann et al, 2005 andHe et al, 2007). The activation of GDNF pathway probably is related with other pathways that promote the proliferation and the self-renewal of SSCs (Caires et al, 2010;Jijiwa et al, 2004;Braydich-Stolle et al, 2007;Oatley et al, 2007 andLee et al, 2006).…”
Section: Characterization Of Spermatogonial Stem Cellsmentioning
confidence: 99%